Stock return volatility and capital structure measures of nonfinancial firms in a dynamic panel model : Evidence from Pakistan - Zeeshan, Ahmed; Daw, Tin Hla (John Wiley & Sons Ltd, 2019)
We investigate the impact of stock return volatility on different capital structure measures of nonfinancial firms in a dynamic panel model. Two‐step system generalized method of moment dynamic panel estimator is applied to nonfinancial sector's data from Pakistan Stock Exchange over the period 2001–2014. The results imply that stock return volatility has a significant negative impact on book leverage and long‐term market leverage ratios. However, stock return volatility causes the increase in total market leverage ratios. Moreover, book leverage and long‐term market leverage of firms decrease as a result of an increase in stock return volatility in different classification of firms. Conversely, stock return volatility has a significant positive impact on total market leverage ratios in those classifications of firms. Capital structure decisions are more sensitive to stock return volatility as default risk increases. Firms significantly go for the reduction in their debt financing due to high stock returns volatility and to avoid from possible consequences of default. The results are robust to alternative measures such as cash flow volatility and earnings volatility.